Polyaniline based polymers in tissue engineering applications: a review. (1st October 2022) - Rai, Ranjana; Roether, Judith A; Boccaccini, Aldo R
Abstract: A number of electrically conducting polymers, such as polyaniline (PANi), as well as functionalized aniline copolymers and composites, which are simultaneously biodegradable and conductive, have been applied for developing electrically conductive scaffolds for tissue engineering (TE) in recent years. The rationale behind these scaffolds is to induce 'electroactivity' in scaffolds, as many research works have shown that an intrinsic electrical activity leads to both increased regeneration rates and improved healing of damaged tissues. PANi is the conductive polymer of choice because it is economical and easy to process with a variety of methods. The resultant PANi based biomaterials have shown biocompatibility, conductivity, suitable processability, positive cellular response, as well as an intrinsic antibacterial effect in numerous research studies. The analysis of the literature has revealed that PANi based scaffolds have been investigated for TE applications including skin/wound healing, bone, cartilage, nerve/spinal cord, vascular, skeletal muscle repair and for the treatment of infertility. Although PANi based materials find widespread applications in other sectors, they are still far away from being commercially exploited as scaffolds for TE despite positive research results. This review aims to discuss and critically assess the current state of PANi based TE scaffolds for different applications. A future perspective for utilizing PANi based biomaterials for applications in TE is discussed, including recent considerations about potential cytotoxic effects.